Reinstatement of the independent specific status of Oldenlandia violacea (Rubiaceae) from the synonymy of O. monanthos - Zhou, Ya-Dong; Amenu, Sara Getachew; Mwachala, Geoffrey; Hu, Guang-Wan; Wang, Qing-Feng (Phytotaxa, 2021)
Oldenlandia violacea (Rubiaceae) was previously treated as a synonym of O. monanthos. However, a detailed examination of the specimens and additional living materials in the field clearly indicated that O. violacea is distinct from O. monanthos in the size of leaves and flowers, and the shape of fruits. The phylogenetic analysis also showed that O. violacea and O. monanthos are nested within Oldenlandia s.str., and could be well separated in the phylogenetic tree. Thus, O. violacea is re-instated here as an independent species.